👤

Descompuneti in factori:
a) [tex](x+ \sqrt{2} ) ^{2} -8[/tex]
b) [tex](2x+ \sqrt{3} ) ^{2} -27[/tex]
c) [tex]( \sqrt{2} x -1) ^{2} -32 x^{2} [/tex]
d) [tex] a^{2} - b^{2} [/tex]
e) [tex] x^{2} - 2\sqrt{3} x +3-(y- 2\sqrt{3} ) ^{2} [/tex]


Răspuns :

(x+√2-2√2)(x+√2+2√2)=(x-√2)(x+3√2)
(2x+√3-3√3)(2x+√3+3√3)=(2x-2√3)(2x+4√3)
(√2x-1-4√2x)(√2x-1+4√2x)=(-3√2x-1)(5√2x-1)
a²-b²=(a_b)(a+b)
asta este formula pe care se bazeaza rezolvarea exercitiilor de acest tip
(x-√3)²-(y-2√3)²=(x-√3-y+2√3)(x-√3+y-2√3)=(x-y+√3)(x+y-3√3)